Sodium benzoate may reduce appetite in Drosophila melanogaster through serotonin upregulation - Nas, John Sylvester B.; Medina, Paul Mark B. (Archives of Biological Sciences, 2025)
Paper description: Sodium benzoate upregulates serotonin. We hypothesized that it induces satiety and activates caloric restriction pathways, driving mechanisms that promote longevity and enhance stress resilience in Drosophila melanogaster. The effects of sodium benzoate on food consumption, lifespan, tryptophan metabolites, Sirt1, and stress resilience were examined in melanogaster. Sodium benzoate reduced food intake, increased serotonin levels, and elevated Sirt1 expression. It extended lifespan under normal and energy-deprived conditions. It did not enhance resilience to heat or UVA-induced stress. Sodium benzoate activates caloric restriction pathways through serotonin upregulation, which supports a role in dietary interventions targeting aging and metabolic health. Abstract: Sodium benzoate is a common artificial preservative in processed food, yet little is known about its long-term health effects. Since sodium benzoate could upregulate serotonin, we hypothesized that it may induce satiety and activate processes underlying caloric restriction that can lead to lifespan extension. In this study, the effects of sodium benzoate on tryptophan metabolism and its potential association with lifespan and stress tolerance in Drosophila melanogaster were investigated. We administered varying doses of sodium benzoate to male and female flies, monitoring their daily food consumption, serotonin levels, kynurenine/tryptophan (kyn/trp) ratio, Sirt1 levels, and survival under normal conditions. Additionally, separate groups of flies were exposed to stressors such as heat, ultraviolet A (UVA) radiation, and energy deprivation to assess the compound’s effects on lifespan under diverse stress conditions. Our results demonstrated that fruit flies fed sodium benzoate exhibited reduced food consumption, decreased kyn/trp ratio, and increased serotonin. The expression of Sirt1, an indicator of the effect of caloric restriction, increased. Their lifespan was prolonged under normal and energy-deprived conditions but was unaffected under heat and UVA stress. Overall, our findings are consistent with our hypothesis that the upregulation of Sirt1 through sodium benzoate supplementation is associated with increased serotonin levels, which may explain delayed senescence and resilience under energy-deprived conditions.